The Impact of Quality Assurance Measures on Academics’ Professional Practices: A Case Study at the Mauritius Institute of Education - Beefun, Roodradeo (2018)
Most Tertiary Education Institutions (TEIs) have set up quality assurance processes to ensure quality of teaching and learning. The importance of quality assurance mechanisms in TEIs is revealed in the literature review which commends that clearly defined and effective quality assurance (QA) policies are necessary.The purpose of this study is to explore academics’ understanding on the impact of QA practices on their professional practices in a TEI at the Mauritius Institute of Education (MIE). Data for this research has been gathered from the analysis of selected institutional texts on QA and in-depth interviews carried out with academics from different departments, schools and with varying years of experience at the institution. The data were analysed, segmented into categories to look at relationship and patterns. The phenomenon of QA in a specific context has been investigated through a qualitative research approach. The findings of this study show that academics viewed QA practices as positive. The academics described that the implementation of QA has led to quality in academic and administrative practices in higher education and has also contributed to standardization, transparency and quality in teacher training. The empirical data confirmed that there is a wide gap between the expectations of academics with regard to QA processes and what actually has been accomplished. The study suggested that the lack of an established institutional text on QA processes and procedures of how QA should be carried out confine the implementation of QA initiative at institutional level. There is a clear indication from the respondents of this study that the relationship between quality and quality assurance is not well defined. One of the key findings of this study is that the academics forcefully defended the boundaries of academic work and felt that the additional burden associated with an increasing change. QA practices have just been added into the traditional scope of academic work An important conclusion can be drawn from this research is that the apparent complexities for implementing an effective QA mechanism in this particular context are mainly due to the lack of participation, cooperation and involvement between academic staff and institutional management.